SARS‐CoV‐2 surveillance in Norway rats (Rattus norvegicus) from Antwerp sewer system, Belgium. Issue 5 (10th July 2021) - Colombo, Valeria Carolina; Sluydts, Vincent; Mariën, Joachim; Vanden Broecke, Bram; Van Houtte, Natalie; Leirs, Wannes; Jacobs, Lotte; Iserbyt, Arne; Hubert, Marine; Heyndrickx, Leo; Goris, Hanne; Delputte, Peter; et al.
Abstract: SARS‐CoV‐2 human‐to‐animal transmission can lead to the establishment of novel reservoirs and the evolution of new variants with the potential to start new outbreaks in humans. We tested Norway rats inhabiting the sewer system of Antwerp, Belgium, for the presence of SARS‐CoV‐2 following a local COVID‐19 epidemic peak. In addition, we discuss the use and interpretation of SARS‐CoV‐2 serological tests on non‐human samples. Between November and December 2020, Norway rat oral swabs, faeces and tissues from the sewer system of Antwerp were collected to be tested by RT‐qPCR for the presence of SARS‐CoV‐2. Serum samples were screened for the presence of anti‐SARS‐CoV‐2 IgG antibodies using a Luminex microsphere immunoassay (MIA). Samples considered positive were then checked for neutralizing antibodies using a conventional viral neutralization test (cVNT). The serum of 35 rats was tested by MIA showing three potentially positive sera that were later negative by cVNT. All tissue samples of 39 rats analysed tested negative for SARS‐CoV‐2 RNA. This is the first study that evaluates SARS‐CoV‐2 infection in urban rats. We can conclude that the sample of rats analysed had never been infected with SARS‐CoV‐2. However, monitoring activities should continue due to the emergence of new variants prone to infect Muridae rodents.